Acoustic insights into the zooplankton dynamics of the eastern Weddell Sea. (May 2016) - Cisewski, Boris; Strass, Volker H.
Highlights: ADCP velocity and backscatter data indicate zooplankton behaviour and abundance. 3-yr time series recorded by moored ADCPs at 3 locations in the Weddell Sea. Zooplankton diel vertical migration symmetric around noon but seasonally asymmetric. Interannual variation of zooplankton abundance as high as annual cycle amplitude. Magnitude of phytoplankton spring bloom possibly controlled by zooplankton grazing. Abstract: The success of any efforts to determine the effects of climate change on marine ecosystems depends on understanding in the first instance the natural variations, which contemporarily occur on the interannual and shorter time scales. Here we present results on the environmental controls of zooplankton distribution patterns and behaviour in the eastern Weddell Sea, Southern Ocean. Zooplankton abundance and vertical migration are derived from the mean volume backscattering strength (MVBS) and the vertical velocity measured by moored acoustic Doppler current profilers (ADCPs), which were deployed simultaneously at 64°S, 66.5°S and 69°S along the Greenwich Meridian from February, 2005, until March, 2008. While these time series span a period of full three years they resolve hourly changes. A highly persistent behavioural pattern found at all three mooring locations is the synchronous diel vertical migration (DVM) of two distinct groups of zooplankton that migrate between a deep residence depth during daytime and a shallow depth during nighttime. The DVM was closely coupled to the astronomical daylight cycles. However, while the DVM was symmetric around local noon, the annual modulation of the DVM was clearly asymmetric around winter solstice or summer solstice, respectively, at all three mooring sites. DVM at our observation sites persisted throughout winter, even at the highest latitude exposed to the polar night. Since the magnitude as well as the relative rate of change of illumination is minimal at this time, we propose that the ultimate causes of DVM separated from the light-mediated proximal cue that coordinates it. In all three years, a marked change in the migration behaviour occurred in late spring (late October/early November), when DVM ceased. The complete suspension of DVM after early November is possibly caused by the combination of two factors: (1) increased availability of food in the surface mixed layer provided by the phytoplankton spring bloom, and (2) vanishing diurnal enhancement of the threat from visually oriented predators when the illumination is quasi-continuous during the polar and subpolar summer. Zooplankton abundance in the water column, estimated as the mean MVBS in the depth range 50–300 m, was highest end of summer and lowest mid to end winter on the average annual cycle. However, zooplankton abundance varied several-fold between years and between locations. Based on satellite and in situ data of chlorophyll and sea ice as well as on hydrographic measurements, the interannual and spatial variations of zooplankton mean abundance can be explained by differences in the magnitude of the phytoplankton spring bloom, which develops during the seasonal sea ice retreat. Whereas the vernal ice melt appears necessary to stimulate the blooming of phytoplankton, it is not the determinator of the blooms magnitude, its areal extent and duration. A possible explanation for the limitation of the phytoplankton bloom in some years is top-down control. We hypothesise that the phytoplankton spring development can be curbed by grazing when the zooplankton had attained high abundance by growth during the preceding summer.